Współczesne standardy w zakresie zarządzania bezpieczeństwem i higieną pracy: między teorią a praktyką - (:unkn) unknown (Wydawnictwo Politechniki Łódzkiej, 2012)
[...] „Współczesne standardy bezpieczeństwa i higieny pracy - między teorią a praktyką" to monografia interdyscyplinarna prezentująca wybrane problemy z zakresu bezpieczeństwa i higieny pracy. Celem monografii jest zaprezentowanie zagadnień związanych z bezpieczeństwem i higieną pracy, które wpływają na proces skutecznego zarządzania organizacją. Zależy nam na przedstawieniu problematyki, która jest w sposób niedostateczny zaprezentowana lub może wzbudzać kontrowersje w gronie osób zajmujących się zarządzaniem bezpieczeństwem i higieną pracy. Monografia jest adresowana zarówno do pracowników naukowych, studentów, jak również do pracowników służb BHP, oraz wszystkich tych, którzy mają zamiar zajmować się problematyką bezpieczeństwa i higieny pracy. Prezentowana monografia składa się z 3 części obejmujących zagadnienia związane z praktycznymi aspektami zarządzania bezpieczeństwem i higieną pracy, zagadnienia procesu szkoleń i kształcenia w zakresie budowania kultury bezpieczeństwa, psychologicznym aspektem funkcjonowania człowieka w organizacji, w powiązaniu z zarządzaniem procesem bezpieczeństwa i higieny pracy. Omówione zostały zagadnienia dotyczące analizy procesu bezpieczeństwa uwzględniające zarówno perspektywę pracownika, jak również problemy związane ze sferą techniczną i organizacyjną powiązane z zarządzaniem bezpieczeństwem i higieną pracy.[...]

The care of human health is the highest value not only from the humanitarian viewpoint but also in the context of social and economic values. This is a wider perspective on people and their functioning in the environment - especially the work environment - which demands systemie approach toward occupational health and safety to change the mentality of polish employers and employees. It seems that recently there are more and more supporters of OHS teaching and increasing the quality of safety ( organizations see the advantages of rational approach to safety matter). On the other hand the model of eliminating the consequences rather than creating the proper work conditions is very popular in polish economy. Despite the development of the systemie management directed at proactive activities like training, motivating to safe work, participation of workers etc. the level of safety in polish enterprises is stili not satisfying. lt is believed that providing protection in accordance with law regulations and improving work conditions mean mainly extra costs and do not give measurable profits. (compare: Znajmiecka-Sikora, Boczkowska, Niziołek, Sikora, 2009; Znajmiecka-Sikora, Boczkowska, Niziołek, Sikora, 201 O). Both the managers and employees of many enterprises do not treat the problem of safety as their own and pay too little attention to this matter. Moreover, the large amount of law regulations and their ambiguity rather discourage than motivate to develop proper habits and approaches toward safety. The control organs increase this discouragement by punishment system which is much more complex and much more often used than the prize system. In practice, this means that enterprises - especially the small and the medium ones - resign from activities connected with safety ( compare: ZnajmieckaSikora, Boczkowska, Niziołek, Sikora, 2009; Znajmiecka-Sikora, Boczkowska, Niziołek, Sikora, 2010). However, the effective system of OHS management together with preventing activities not only enable law-respecting and efficient functioning of enterprise, but also give measurable economic profits (minimalizing loss by eliminating accidents and occupational diseases) and social benefits (employee's motivation toward safety behaviour, awareness of hazards and ways of preventing). Good work conditions, high-tech culture, low rate of accidents and less amount of occupational diseases reduce the costs connected with work, which has a great signification not only for individuals but for the whole country. The basis of safety management is the belief that safe conditions and safe behaviour have to be developed by following the established programme (Lewandowski, 2000). ,,The Modern Management Standards of Occupational Safety and Health - between theory and practice" is the interdisciplinary monograph which presents selected problems in the OHS field. The aim of the monograph is to present issues connected with OHS, which are significant for the process of effective organizational management. We would like to discuss the problematic aspects which have not been discussed so far in a satisfying way or which are controversial among individuals connected with OHS management. The monograph is dedicated to academic workers, students, OHS providers and everyone who is interested in OHS problematic aspects. The materiał consists of 3 parts and presents practical aspects of OHS management, training process in the contexts of building the safety culture, psychological aspects of functioning man in the organization in the context of managing the OHS process. The issues take into consideration the human perspective, problems connected with the technical sphere and the OHS management. The monograph was written by representatives of the science world and practitioners - those who are responsible for safety in enterprises and who work as the consultants or trainers. The authors belong to different groups of professionals: OHS providers, expert witnesses, doctors, psychologists, chemists, academic workers. This diversity confirm the complexity and interdisciplinarity of the OHS problematic aspects.
Red. nauk. Wydziału : Lewandowski, Jerzy
Keywords: bezpieczeństwo pracy - zarządzanie; bezpieczeństwo pracy - normy; higiena pracy - zarzązanie; bezpieczeństwo pracy - aspekt psychologiczny; work safety - management; work safety - standards; occupational hygiene - management; work safety - psychological aspect